Mitochondrial microRNAs (mitomiRs) as emerging biomarkers and therapeutic targets for chronic human diseases - Méndez-García, Andrea; García-Mendoza, Marely Abigail; Zárate-Peralta, Carmila Patricia; Flores-Perez, Fernanda Valeria; Carmona-Ramirez, Luis Fernando; Pathak, Surajit; Banerjee, Antara; Duttaroy, Asim K.; Paul, Sujay (Frontiers in Genetics, 2025)
Mitochondria are membrane-bound cell organelles that undertake the majority of the energetic and metabolic processes within the cell. They are also responsible for mediating multiple apoptotic pathways, balancing redox charges, and scavenging reactive oxygen species. MicroRNAs, which are short, non-coding RNAs widely known for regulating gene expression at the post-transcriptional level, regulate many of these processes. The specific microRNAs that directly or indirectly control mitochondrial dynamics are called mitochondrial miRNAs (mitomiRs). The broadest classification of this type of ncRNA encompasses nuclear-encoded miRNAs that interact with cytoplasmatic mRNAs associated with mitochondrial activity. At the same time, a more specific subset comprises nuclear-encoded miRNAs that translocate into the mitochondria to interact with mRNAs inside of this organelle. Finally, the smallest group of mitomiRs includes those codified by mtDNA and can regulate endogenous mitochondrial transcripts or be transported into the cytoplasm to modulate circulating mRNAs. Regardless of the origin or action mechanism, mitomiRs have been recently recognized to have a key role in the progression of a variety of chronic disorders, such as neurodegenerative and cardiovascular diseases, diabetes, asthma, depression, and even cancer. All of these progressive pathologies have been tightly linked to mitochondrial dysregulation. They are further associated with an aberrant expression of specific miRNAs that regulate cellular metabolism, positioning mitomiRs as reliable biomarkers for diagnosing several chronic diseases. These molecular indicators have also provided insights into how these conditions progress, allowing for the development of different miRNA-based treatment strategies that target dysregulated mitochondrial-related genes, reestablishing their baseline activity and restricting further disease progression.